Analisis Faktor yang Memengaruhi Minat Masyarakat Terhadap Wakaf di Kota Tangerang Selatan - Pratama, Juliyan Surya Pratama; Naufal, Muhammad; Haqiqi, Fadhlan; Kurniyawan, Reza; Yaasin, Muhammad Syafa'at (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2024)
This study examines the factors influencing public participation in cash waqf in South Tangerang City, focusing on media information, religiosity, knowledge, education, and income levels. Utilizing a quantitative approach, primary data were collected from 100 respondents through structured questionnaires and analyzed using multiple regression. The findings reveal that media information, religiosity, education level, and income level significantly impact interest in cash waqf, while knowledge level does not show a significant effect. The regression model explains 82.2% of the variance in waqf participation, indicating a strong influence of the independent variables on public interest. These results highlight the importance of accessible and effective media campaigns, as well as enhanced religious education, to improve public engagement in cash waqf practices.